Risk Mitigation in Village Financial and Asset Management: Evidence from Boyolali Regency - Purnama, Yunus Indra; Junaidi; Mahsun, Mohamad (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The increasing allocation of village funds in Indonesia has raised concerns about the integrity and accountability of financial reporting at the village level. This study analyzed potential fraud risks in village financial reporting in Boyolali Regency using the fraud diamond framework, which includes pressure, opportunity, rationalization, and capability. A descriptive qualitative method was employed through content analysis of 115 villages in 10 districts based on document reviews, structured interviews, and expert evaluations. The study develops a semi-quantitative risk matrix to classify and map risks according to the frequency and impact of internal control weaknesses. The findings reveal systemic vulnerabilities throughout all stages of village financial management, from planning and implementation to reporting and asset accountability. Opportunity-related factors, such as lack of document verification, low transparency, and weak internal controls, are the main drivers of fraud risk. The dominance of village heads in decision-making and the limited technical capacity of village officials further increase fraud potential. This study proposes a comprehensive risk mapping model and practical recommendations, including strengthened verification mechanisms, enhanced human resource capacity, risk-based internal controls, digitalized reporting systems, and community oversight to promote preventive and accountable public financial governance at the village level.